Acute heart failure due to myocarditis in Takayasu's arteritis - M.d.L. Castro de Oliveira Figueirôa; M.C. Moura Costa; P. Rocha Lobo; A.L. Souza Pedreira; M. Barreto Santiago (Reumatismo, 2024)
Takayasu’s arteritis (TA) is a granulomatous vasculitis that involves the aortic artery and its branches, resulting in stenosis, occlusion, and aneurysmal dilatation. Cardiovascular involvement is one of the main complications and a major cause of mortality in these patients. Herein, we describe the case of a woman with TA who presented with severe acute heart failure secondary to myocarditis and responded well to immunosuppressive therapy.